ANALISIS DETERMINAN FUNDAMENTAL TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI BURSA EFEK INDONESIA - Irma Andriani; Rizkia Ramadhani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to dissect the extent to which fundamental determinants measured through the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF) and Operational Costs to Operating Income (BOPO) affect the level of profitability (Return on Assets) in Islamic commercial bank. The observation focuses on 4 (four) Islamic banks listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period. Using a quantitative approach, the data estimation is calculated through panel data regression assisted by Eviews software. Empirical test results reveal that collectively, the three fundamental ratios have a significant effect on ROA. However, partial analysis proves that cost inefficiency (BOPO) and high non-performing financing (NPF) are the primary factors most noticeably suppressing profitability. On the other hand, the size of the capital buffer (CAR) does not show a meaningful statistical impact on profit growth. These findings provide a strong signal for banking management to prioritize operational efficiency and financing quality over mere aggressive expansion.Keywords: BOPO, CAR, NPF, ROA